Strategi Pembelajaran Diferensiasi dalam Kelas Heterogen English Starter di ADPBI Horu Kane English Course - Que, Stella Rose; Refualu, Luis Harry Anasyama (Universitas Pattimura, 2025)
This community service activity was carried out through the English Starter class at ADPBI Horu Kane English Course with the aim of providing basic English support for students from diverse educational backgrounds and varying levels of prior knowledge. The design of the activity employed an adaptive learning approach tailored to individual needs. The implementation was divided into three stages: first, a diagnostic assessment to map students’ initial abilities through basic material introduction and short interviews; second, lesson design using worksheets with varying levels of difficulty but focusing on the same core material; and third, formative evaluation at the end of each session to measure students’ understanding. Observations over one month indicated that student attendance became more consistent, motivated by their success in completing worksheets adjusted to their level. Students also grew more confident in using simple classroom phrases, while the challenge of differing learning speeds was addressed through peer tutoring. This activity demonstrates that adaptive learning strategies can enhance motivation, confidence, and participation in heterogeneous classes. Therefore, the program not only strengthened students’ basic English foundation but also provided an inclusive learning model that can be applied in similar contexts.